Challenging Access to Land in Central European Countries: Some Comments on the “Bundle of Rights” and “Webs of Power” - Marie-Claude Maurel (Wieś i Rolnictwo)
Access to land is often presented as a matter of simple national legal norms. This article develops an empirical analysis of how the conditions of access to farm land were set up in the wake of the restoration of private property as part of the transition to a market economy, and then changed following the accession of Central European countries to the EU. It shows how legal and social norms overlap, combine and contradict each other, reflecting the evolving power dynamics between land holders, land owners or farmers, land-market control agencies and national authorities. Land concentration is the result of competition between social actors to capture and consolidate a “bundle of rights” over land and capital. Recent changes in land-tenure regulations have eased the emergence of “webs of power” that are characteristic of a new agrarian capitalism.